What Motivate Youths to Start a Business: An Empirical Evidence from Eastern Nepal - Rai, Arjun; Rai, Chandra Kumar; Adhikari, Khagendra; Karki, Min Bahadur (Journal of Management, 2021)
This survey attempted to explore the motivating factors of young entrepreneurs in eastern Nepal to start a business. Primary data were collected from 204 young entrepreneurs from eastern Nepal using a self-administered questionnaire. The collected data were coded, entered, and processed in the Statistical Package for the Social Science (SPSS, version 25). This survey used a quantitative technique to analyze the collected data. The study's findings revealed that most young entrepreneurs of eastern Nepal were motivated by profit potential to start the business, followed by a perceived difficulty tofind a job in Nepal and willingness to do something new through entrepreneurial activity. The least number of entrepreneurs had started their business for legacy purposes and to take advantage of a supportive business network.